Trichoderma azadirachtae sp. nov. from rhizosphere soil of Azadirachta indica from Guangdong Province, China - Huang, Qiu-Rong; Senanayake, Indunil C.; Liu, Jia-Wei; Chen, Wen-Jing; Dong, Zhang-Yong; Luo, Mei (Phytotaxa, 2024)
Trichoderma species are distributed worldwide and they play an important role in plant protection, growth promotion and also as biocontrol agents of plant diseases. In this study, a new species of Trichoderma was isolated from Azadirachta indica rhizosphere soils in Zhaoqing City, Guangdong Province, China. Based on the morphology and combined multigene phylogeny of nuclear internal transcribed spacer of rDNA region (ITS), translation elongation factor 1 alpha (tef1-α) and RNA polymerase second largest subunit (rpb2), a new Trichoderma species belongs to the Harzianum-clade was identified, namely Trichoderma azadirachtae sp. nov. Distinctions between the new species and its close relatives are discussed in detail.